1995
DOI: 10.1002/chin.199550098
|View full text |Cite
|
Sign up to set email alerts
|

ChemInform Abstract: Condensation of 2‐Arylidene‐1,3‐indandiones with Antipyrine and Indole.

Abstract: ChemInform is a weekly Abstracting Service, delivering concise information at a glance that was extracted from about 100 leading journals. To access a ChemInform Abstract of an article which was published elsewhere, please select a “Full Text” option. The original article is trackable via the “References” option.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
12
0
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 0 publications
2
12
0
1
Order By: Relevance
“…Addition of the anion 14 to 2 lead to the intermediate 8, which reacts with piperidine and formaldehyde to give 9 as the end product. The cleavage of the phenylaminobenzyl residue from 5d and formation of 8 as intermediate is in line with the reported deaminobenzylation [19] and deaminomethylation [20], of Mannich bases in basic medium with subsequent formation of benzylidene or methylenebisderivatives (Scheme 5).…”
Section: Proposed Mechanism For Formation Of Compoundsupporting
confidence: 89%
See 1 more Smart Citation
“…Addition of the anion 14 to 2 lead to the intermediate 8, which reacts with piperidine and formaldehyde to give 9 as the end product. The cleavage of the phenylaminobenzyl residue from 5d and formation of 8 as intermediate is in line with the reported deaminobenzylation [19] and deaminomethylation [20], of Mannich bases in basic medium with subsequent formation of benzylidene or methylenebisderivatives (Scheme 5).…”
Section: Proposed Mechanism For Formation Of Compoundsupporting
confidence: 89%
“…Further reaction of 2 with 14 lead to 8, which undergo Mannich reaction with piperidine and formaldehyde to give the end product 9. The deamination of 5d is in line with many reported cases in which free Mannich bases undergo deamination spontaneously [18,19], to give unsaturated products. On the other hand, the tendency of 5d to undergo deaminobenzylation is enhanced by the presence of the strong base piperidine (pkb 2.80), which abstracts a proton from 5d to give the carbanion (11), which is stabilized by delocalization of its charge (12 ↔ 13.…”
Section: Proposed Mechanism For Formation Of Compoundsupporting
confidence: 87%
“…Die eher moderate Ausbeute resultiert daher, dass 1 unter sauren Bedingungen zum pentacyclischen Derivat 11 weiter reagiert (Schema ). Daher haben wir in Betracht gezogen, die Friedel‐Crafts‐Alkylierung unter basischen Bedingungen durchzuführen,15 da unter diesen Bedingungen 11 nicht auftreten sollte. Für die basische Friedel‐Crafts‐Alkylierung mussten wir 10 von der Säure befreien und als Rohprodukt isolieren, bevor wir 2 in THF mit zwei Äquivalenten NaH deprotonierten und anschließend mit 10 umsetzten.…”
Section: Methodsunclassified
“…Afsah et al reported the Michael‐type reaction of 2‐(arylmehylene)‐1 H ‐indene‐1,3(2 H )‐dione 10 with compound 1 in refluxing ethanol to afford 2‐aryl(1,5‐dimethyl‐3‐oxo‐2‐phenyl‐2,3‐dihydro‐1 H ‐pyrazol‐4‐yl)methyl‐1 H ‐indene‐1,3‐(2 H )‐diones 11 . …”
Section: Reactions With Antipyrine: Formation Of 4‐substituted Antipymentioning
confidence: 99%